Development of smart parking system using internet of things concept - Dwi Puspitasari; Noprianto Noprianto; Muhammad Afif Hendrawan; Rosa Andrie Asmara (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
The growing number of vehicles in developing countries causes a slew of issues, including the parking system.The current parking system is mostly manual, requires human intervention as a security system, and does not provide information about available parking areas.Their problems cause nonoptimal parking management. Furthermore, it can lead to income loss and criminal acts. This study addresses one of the possible solutions by using the internet of things (IoT) concept. The parking system is built by utilizing a smart card, machine-to-machine (M2M) communication, and cloud monitoring. As a result, the smart parking system prototype has been provided. The parking system business process can be done automatically, and it provides a more secure parking security system. The proposed parking system architecture also provides a practical system. The system only took around 1 second to perform the data transmission between nodes.